Optimization of Health Communication Strategies and Guidance of Digital Health Behaviors: A Critical Review of Jiang Li’s Research - Yang, Han (The Journal of Medicine, Humanity and Media, 2026)
Currently, with the advancement of social economy and the growing public awareness of health, health communication has emerged as a crucial pathway to enhance public physical health and improve people’s quality of life. Theoretical innovation and practical translation in this field have garnered significant academic and practical attention. Jiang Li, Associate Professor in the Department of Media and Communication at City University of Hong Kong, has long been deeply engaged in health communication research, producing influential scholarly works on topics such as vaccination and mobile health. This study systematically synthesizes her academic achievements in health communication, conducting a detailed analysis from the dimensions of research context, research characteristics, and research contributions. It aims to reveal the developmental trajectory of her health communication research and provide valuable insights for future studies in this field.